Pengaruh Kualitas Pelayanan dan Kualitas Produk Kredit UKM Terhadap Loyalitas Nasabah PT. BPR Kerta Raharja Bandung - Indra Prabhata (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
This research investigated how big the effect service quality on the customer loyality of the PT BPR Kerta Raharja Bandung, investigated how big the effect of product quality on the customer loyality of the PT BPR Kerta Raharja Bandung, investigated how big the effect of service quality and product quality by simultaneous on the customer loyality of PT BPR Kerta Raharja Bandung.This research was used corelation methode to investigated how big the effect of dependent and independent variables. The research population is 576 customers of PT BPR Kerta Raharja and 85 peoples to be sampling in this research. Each respondents was given 30 questions by using likert scale.Based on the data processing, indicated the effect of service quality on customer loyality of the PT BPR Kerta Raharja is very adequate means that the relation between those variables significant on the degree of strong level. the effect of product quality on customer loyality of the PT BPR Kerta Raharja is very adequate means that the relation between those variables significant on the degree of strong level. The last, the effect of service quality and product quality on customer loyality of the PT BPR Kerta Raharja is very adequate means that the better of service quality and product quality, to further improve customer loyality.